STRATEGI MENINGKATKAN HASIL BELAJAR SELAMA PANDEMI DENGAN APLIKASI GOOGLE CLASSROOM PADA MATERI USAHA DAN ENERGI - Franciska Ayuningsih Ratnawati (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
This study aims to determine the improvement in learning outcomes of students at class of X MIPA 2, SMA Negeri I Gamping, Sleman by utilizing the google classroom application as one of learning strategies during the Covid-19 pandemic on the subject work and energy. This study is a classroom action research conducted during two cycles. Each cycle consists of planning, action, observation, and reflection. Learning strategies utilized the google classroom application. The advantage of this application is learning management became easier for teachers and convey information precisely and accurately for students. The results of this study indicate that the learning strategy utilizing technology in the form of google classroom application during Covid-19 pandemic can improve student learning outcomes on the subject work and energy in class X MIPA 2 SMA Negeri I Gamping Sleman. The test result at the end of the first cycle showed 6 students with a percentage of completeness 18%. There was an increase in the percentage of completeness in second cycle, i.e 94% from 31 students. Result of this study describe that the target percentage of students completeness has exceeded the minimum limit value.